Shiny Apps in Distance Education: Do Psychology Students Benefit From Interactive Statistics Applications? - Eric Berkmann; Björn Fisseler; Lena Schützler; Oliver Christ (Journal of Statistics and Data Science Education)
The development of Shiny, a web framework for R, has greatly simplified the process of creating interactive statistical applications. The principal objective of this study was to evaluate the implementation of Shiny applications in distance learning for a diverse student cohort. A longitudinal study was conducted with a quasi-experimental design, employing propensity score matching to compare two cohorts of 524 and 773 students at the FernUniversität in Hagen, Germany. Data were collected on students’ academic performance, perception of statistics, and evaluations of the Shiny apps. The results indicated no significant difference in academic performance between the intervention and control groups. However, students’ perception of statistics changed significantly throughout the semester, and group membership did not moderate these time-related changes. Despite this, the majority of students expressed positive attitudes toward the Shiny apps and found them beneficial for their studies. This article discusses the implications of using Shiny apps in distance education and potential directions for future research. Supplementary materials for this article are available online.